Маркетинг взаємодії в підприємствах зернопродуктового комплексу АПК - Арестенко, Тетяна Вікторівна; Арестенко, Татьяна Викторовна; Arestenko, Tetiana; Арестенко, В. В. (My University, 2016)
У статті розглядаються питання маркетингу взаємодії у підприємствах АПК. Пропонований підхід сприяє отриманню справедливої норми прибутку в зернопродуктовому комплексі АПК всіма учасниками шляхом більш детальних та довірливих відносин, ціннісної орієнтації та підвищення конкурентоспроможності підприємств за рахунок кращих, ніж у конкурентів, способів взаємодії з партнерами по агробізнесу. Основну увагу приділено партнерським відносинам з ключовими клієнтами сільськогосподарських підприємств, а саме переробними підприємствами. Interaction of business of the agricultural market in the increasingly competitive relationship determines the need to find new forms and methods of strategy and tactics farm to gain advantages and maintenance market. The article describes main questions of marketing cooperation in agricultural enterprises. Feature of marketing interaction is that in its implementation it up long-term, multifaceted business nets between producers, suppliers and buyers. Circle functions with market research, marketing planning and communication processes, sales promotion and pricing is also carried interaction function proposed approach helps to ensure fair rate of return in the agribusiness sector of grain production. In the article discover the way of formation more detailed and trusting relationships, value orientation and competitiveness of enterprises through better than competitors, interactions with partners in the agribusiness. The analysis of the economic efficiency of farms Zaporozhye region, specializing in the production of grain (and including barley) and economic bases of interaction with enterprises processing and sale of processed products in grain production revealed that further effective development grain production complex Zaporozhye region as a whole can only be achieved through vertical business combination. The focus partnership with key clients farms, namely processors is build. The proposed approach helps to ensure a fair rate of return in the grain production agribusiness sector all participants by more detailed and trusting relationships, value orientation and competitiveness of enterprises through better than competitors, interactions with partners in the agribusiness.
Keywords: маркетинг взаємодії; партнерські відносини; маркетингові комунікації; сільськогосподарське підприємство; зернопродуктовий комплекс; marketing; behavior marketing; partnership business relations; marketing communications; agricultural enterprises; grain production